Pengaruh Copywriting Tiktok Hyalucera Moisturizer The Originote terhadap Minat Beli Masyarakat - Aisha Isaura Karno; Bambang Sujarwadi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The digital era development brings many factors that influence people's purchase intention, especially through digital marketing communication content. This study aims to identify whether copywriting in TikTok hyalucera moisturizer The Originote partially and simultaneously affect public purchase intention using quantitative research methods. The population in this study involves people who have and have not become consumers of the product so that it is infinite with a sample of 100 respondents obtained through simple random sampling. The results of the research analyzed using the IBM SPSS Statistics 26 program show that the copywriting elements of attention (X1) and communicate (X2) have no positive and significant effect partially with a value of 1.259 and a significance value of 0.211 for X1 and -0.519 with a significance value of 0.605 for X2. Meanwhile, the persuade (X3) and conviction (X4) variables have a positive and significant partial effect on people's purchase intention with a value of 3.482 and a significance value of 0.001 for X3 and a value of 3.958 with a significance value of 0.000 for X4. Copywriting elements simultaneously have a positive and significant effect on public purchase intention with an value of 57.329 and a significance value of 0.000. Based on the coefficient of determination (R2) test, copywriting elements have a positive and significant effect on purchase intention (Y) of 70.7% with the remaining 29.3% influenced by other factors not included in this study. Suggestions that can be given for variables X1 and X2 are making titles using the 4 U's formula and creating message content using the you-orientation method because good copywriting not only persuades and convinces, but also must attract attention and communicate.